PSICOMOTRICIDADE E EDUCAÇÃO MUSICAL: REFLEXÕES PARA O DESENVOLVIMENTO PSICOMOTOR DA CRIANÇA ATRAVÉS DO MÉTODO DE DALCROZE - Augusto Paulucci Ribeiro; Janaina Pereira Duarte Bezerra (Universidade do Oeste Paulista, 2015)
This article aims to reflect, through a bibliographic study on the relationship between music education and psychomotor from the Dalcroze method and psychomotor education field - Psychomotor Functional. Approaching these aspects and highlighting activities of proposals that can contribute to the psychomotor development of children, also was intended to expand the possibilities of conducting a teaching job by music teachers and teachers of elementary schools regarding the use the playful and respecting cognitive ability, emotional, social, emotional and motor child according to their age group.